Marine fuel refining technology improvement trade-offs: a game theoretic approach - Zhou, Qin (2022)
The implementation of International Maritime Organization (IMO) 2020 sulfur cap requires ship operators to decrease fuels’ sulfur content and this may increase their demand for low-sulfur fuel (LSF). In anticipation, bunker companies can choose to upgrade their refining technology to produce better quality distillate and lighter oil. In this study, we consider a bunker supply chain consisting of bunker companies and a population of ship operators with two main marine fuel products, low-sulfur fuel (LSF) and high-sulfur fuel (HSF). We use Cournot game to model the competition between LSF and HSF under two different market channels (i.e., dual and single channels). The results show that bunker companies’ refining technology upgrading choice is affected by many operational parameters, such as the basic market demand, cost difference between LSF and HSF, market competition, variable and fixed cost for upgrading, the increase of market demand due to upgrading, and so on. Compared with a dual channel bunker company, a single channel bunker company is less likely to implement new refining technology. We further consider the scenario where bunker companies can make decisions after the realization of ship operators’ demand uncertainty. The findings are beneficial for both LSF and HSF bunker companies and may reach a win-win solution for bunker companies.